THE EFFECT OF ORGANIZATIONAL CULTURE AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENING VARIABLE AT PT SUPRA PRIMATAMA NUSANTARA TERRITORY WEST 1 - SUMATRA - Hutapea, Winda Melina; Toni, Nagian; Rostina, Cut Fitri; Romy, Elly (Social Economics, 2024)
The research objective of this article is to examine the factors that influence Organisational Culture and Work Motivation on Employee Performance. The development of an increasingly broad and complex business world has an impact on qualified and competent human resources, which is one of the company’s needs and is the main element that must be managed in order to achieve company goals. Organisational culture has an important impact on performance. Therefore, companies need to form an organisational culture that develops so as to create performance that is aligned with organisational goals. A strong culture will show high agreement on organisational goals among its members. Unanimity towards goals will form attachment, loyalty, and organisational commitment, this condition will further reduce the tendency of employees to leave the organisation. In addition to organisational culture, work motivation is a factor that can affect employee performance. Therefore, to achieve its goals, a strategy is needed to create organisational culture and work motivation. Theoretical and practical aspects, culture brings a sense of identity for members of the organisation, forming high organisational commitment in each member, shaping employee attitudes and behaviour, both in interacting internally and externally to the organisation. And Motivation is believed to increase the productivity of each employee, increase the work enthusiasm of each employee, increase the work creativity of each employee and increase the loyalty of each employee to the company. This research was conducted at PT Supra Primatama Nusantara (Biznet) Territory West 1 - Sumatra with 72 people. The inductive analysis map shows that organisational culture and work motivation on employee performance have a positive and significant effect on employee performance. The direction of influence of this variable is also positive, which means that the better organisational culture of an organisation will increase job satisfaction and good Work Motivation will provide enthusiasm and positivism in carrying out its performance.